197k views
1 vote
5 (u + 1) -
7 = 3
3 (u - 1) + 2u​

1 Answer

6 votes

Final answer:

The equation 5(u + 1) - 7 = 33(u - 1) + 2u is a linear equation that can be solved by applying the distributive property, combining like terms, and then isolating and solving for the variable u, yielding the solution u = 31/30 or about 1.0333.

Step-by-step explanation:

The equation provided by the student is a linear equation in one variable, which can be solved for the variable u. To solve the equation 5(u + 1) - 7 = 33(u - 1) + 2u, you need to apply distributive property first, then collect like terms, and finally solve for u by isolating it on one side of the equation.

  1. Apply the distributive property: 5u + 5 - 7 = 33u - 33 + 2u.
  2. Combine like terms: 5u - 2 = 35u - 33.
  3. Get all terms with u on one side: -30u = -31.
  4. Divide by the coefficient of u to solve for it: u = 31/30 or approximately 1.0333.

User Berty
by
5.2k points